The apprentice perspective: A blind spot in the governance of VET systems? A German-Danish-Swiss comparison - Hippach-Schneider, Ute [Verfasser]; Grobe-Rath, Janine [Verfasser] (My University, 2023)
"The apprentice's perspective is of central importance for the educational policy design and further development of VET systems. The success of all education policy measures that keep VET attractive or make it more attractive ultimately depends on the educational decisions of learners. It is therefore crucial for a potentially successful VET policy to know the perspective of those who have decided to enter VET. Their assessments and experiences must be systematically incorporated into education policy decisions at the governance level. The paper presents and discusses whether, how and with what content-related focus this takes place. The focus is on the approaches in Germany, Switzerland and Denmark. The project underlying this article is based on the theoretical background of actor-centred institutionalism (Scharpf, 2000) and actor-network theory (Latour, 2007)." (Authors' abstract)
Keywords: S 2.3 Berufsbildungspolitik; P 2.3 Auszubildende; I 2.2.1 Westeuropa; 370; Auszubildender; Perspektive; Kommunikation; Rezeption; Berufsbildungspolitik; Governance; Internationaler Vergleich; Deutschland; Dänemark; Schweiz